2022
DOI: 10.1186/s13045-022-01392-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cell death pathways for cancer therapy: recent developments in necroptosis, pyroptosis, ferroptosis, and cuproptosis research

Abstract: Many types of human cells self-destruct to maintain biological homeostasis and defend the body against pathogenic substances. This process, called regulated cell death (RCD), is important for various biological activities, including the clearance of aberrant cells. Thus, RCD pathways represented by apoptosis have increased in importance as a target for the development of cancer medications in recent years. However, because tumor cells show avoidance to apoptosis, which causes treatment resistance and recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
187
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(188 citation statements)
references
References 359 publications
1
187
0
Order By: Relevance
“…Tong et al, described in a review the mechanisms of necroptosis, pyroptosis, ferroptosis, and cuproptosis and the effects on tumour cell proliferation and cancer metastasis. The authors draw attention onto the potential agents and nanoparticles for cancer treatment or the association of these with already existing therapies inducing RCD compared to conventional treatments [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tong et al, described in a review the mechanisms of necroptosis, pyroptosis, ferroptosis, and cuproptosis and the effects on tumour cell proliferation and cancer metastasis. The authors draw attention onto the potential agents and nanoparticles for cancer treatment or the association of these with already existing therapies inducing RCD compared to conventional treatments [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that ICB treatment may be effective for the C15orf48 high-expression group, but not the low-expression group. Pathway analysis showed that C15orf48 was significantly associated with various pathways, such as apoptosis, P53 pathway, and ferroptosis, which are critical in cancer development and immunotherapy (40,41). Subtype studies have revealed heterogeneity among the different subtypes in THCA.…”
Section: Discussionmentioning
confidence: 99%
“…Xuhui Tong et al, described in a review the mechanisms of necroptosis, pyroptosis, ferroptosis, and cuproptosis and the effects on tumor cell proliferation and cancer metastasis. The authors draw attention to the potential agents and nanoparticles for cancer treatment or the association of these with already existing therapies inducing RCD compared to conventional treatments [55].…”
Section: Cancermentioning
confidence: 99%